Diagnosing dental and orofacial pain : a clinical manual - Moule, A. J. (Alex J.); Hicks, M. Lamar (John Wiley & Sons, Ltd., 2016)
A Clinical Manual. Diagnosis made quick and easy know the right questions to ask when a patient comes to you in pain